PENGARUH PROFESIONALISME DAN KOMITMEN ORGANISASI TERHADAP KINERJA INTERNAL AUDITOR PADA BPK PERWAKILAN DKI JAKARTA - Ratna Ningsih Radjak (Cakrawala Management Business Journal, 2019)
This study aims to determine the Effect of Professionalism and Organizational Commitment on Internal Auditor Performance on DKI Jakarta Representative BPK. The method used to determine the Effect of Professionalism and Organizational Commitment on Internal Auditor Performance uses multiple regression statistical analysis. Based on the research results and hypothesis testing it can be proven that partially the professionalism variable has a positive effect on the performance of the Internal Auditor. While the Organizational Commitment variable significantly influences the performance of the Internal Auditor. Simultaneously the variable Professionalism and Organizational Commitment significantly influence the performance of Internal Auditors. The ability of the variable Professionalism and Organizational Commitment to explain changes in Auditor Performance is equal to 60.8% and the rest is caused by other factors not examined. Of the three variables that most dominantly affect the performance of the Internal Auditor is Professionalism, based on the value of the regression coefficient and the t-level of significance of the Professionalism variable is higher than the Organizational Commitment variable. Thus the Auditor Professionalism really helps the Auditor to improve his performance.